2017
DOI: 10.1016/j.rser.2017.03.078
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment demonstrates environmental co-benefits and trade-offs of low-carbon electricity supply options

Abstract: Printed by Skipnes Kommunikasjon as PREFACE i PREFACE Βουλεύου μὲν βραδέως, ἐπιτέλει δὲ ταχέως τὰ δόξαντα. Be slow in deliberation, but be prompt to carry out your resolves.Isocrates, To Demonicus, ca. 400 B.C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 81 publications
3
61
0
Order By: Relevance
“…In the consequential system model of ecoinvent v.3.4, the linking algorithm is replaced by a so-called Bmarket override^: electricity markets are determined by the procedure described in the previous section and manually 4 According to Gibon et al (2017), biopower technologies can generate life cycle climate change impacts ranging from 28 to 194 kg CO2 eq./MWh. This compares to an impact score of 37 kg CO2 eq./MWh for the created power only bio-energy unit.…”
Section: Comparison Of Methodologies Used In Consequential System Modmentioning
confidence: 99%
See 2 more Smart Citations
“…In the consequential system model of ecoinvent v.3.4, the linking algorithm is replaced by a so-called Bmarket override^: electricity markets are determined by the procedure described in the previous section and manually 4 According to Gibon et al (2017), biopower technologies can generate life cycle climate change impacts ranging from 28 to 194 kg CO2 eq./MWh. This compares to an impact score of 37 kg CO2 eq./MWh for the created power only bio-energy unit.…”
Section: Comparison Of Methodologies Used In Consequential System Modmentioning
confidence: 99%
“…& A set of midpoint categories from the ReCiPe 2008 Midpoint (H) impact assessment method (Goedkoop et al 2008). The selection of impact categories is based on the work by Gibon and colleagues (Gibon et al 2017) in their assessment of low-carbon electricity supply options which are namely: freshwater ecotoxicity, freshwater eutrophication, human toxicity, metal depletion, particulate matter formation, photochemical oxidant formation, terrestrial acidification, and urban land occupation. & Finally, the single score method ReCiPe 2008 Endpoint (H,A) is used to obtain the overall environmental performance of the different marginal electricity supply mixes in a single weighted and normalized indicator (Goedkoop et al 2008).…”
Section: Market Mix/impact Assessment Calculations and Comparative Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies taking this approach have developed LCAs of long term energy scenarios, developing dynamic life-cycle inventories that are fully consistent with the energy mix depicted in the scenario, focusing for example on wind power (Arvesen and Hertwich 2011), renewables in Australia (Wolfram et al 2016) or in Europe (Peter et al 2016), and low-carbon technologies more generally (Hertwich et al 2015). These scenarios are typically generated using energy system optimisation models, such as the IEA's ETP model, a member of the MARKAL/TIMES family, which was used by (Gibon et al 2015;Arvesen and Hertwich 2011;Hertwich et al 2015;Gibon et al 2017). These studies provide valuable insights into the relative environmental impacts associated with various technologies in different possible futures: they have shown that technologies with low use-phase carbon emissions also provide considerable co-benefits (Hertwich et al 2015), as well as performing well in terms of whole-life-cycle carbon emissions (Wolfram et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…From the environmental point of view, emerging PVs are of interest since their thin-film technology is associated with savings of weight and materials. Therefore, the life-cycle impacts of emerging PVs are expected to be lower than those of commercial PVs of the first and second generations.PVs were investigated in a multitude of LCA studies which led to general insight into their life-cycle impacts [8][9][10][11][12][13][14][15], i.e., about 80% of total life-cycle GHG emissions can be attributed to the production stage [15]. However, different LCA studies on PV revealed large differences in results [11,12], an observation that was also made for LCAs of other electricity generation technologies.…”
mentioning
confidence: 99%